2013
DOI: 10.1086/668777
|View full text |Cite
|
Sign up to set email alerts
|

Blood Culture Contamination A Randomized Trial Evaluating the Comparative Effectiveness of 3 Skin Antiseptic Interventions

Abstract: ClinicalTrials.gov identifier: NCT01216761 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
2
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 23 publications
(24 reference statements)
2
26
2
2
Order By: Relevance
“…This study corroborates and supports the recent findings of Washer et al (6). Similar to those investigators, we found virtually no difference in CRs between CH and IT.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This study corroborates and supports the recent findings of Washer et al (6). Similar to those investigators, we found virtually no difference in CRs between CH and IT.…”
Section: Discussionsupporting
confidence: 94%
“…The results of this study, as well as those of Washer et al (6), suggest that iodine tincture and chlorhexidine tincture are equivalent antiseptic agents for skin antisepsis in patients who require blood cultures. Therefore, other factors may be considered in the decision of which product to choose in a given institution.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…7,8 Contaminants have been reported to result in false positive blood cultures in anywhere between 2.4% and 50% of cases. [7][8][9][10][11] These false positive results have been associated with prolonged hospitalisation and a 20% increase in healthcare cost. 12 Blood cultures have been shown to have little effect on clinical management in women with pyelonephritis and acutely unwell surgical patients.…”
mentioning
confidence: 99%